Individualized Integrative Cancer Care in Anthroposophic Medicine: A Qualitative Study of the Concepts and Procedures of Expert Doctors. (December 2016) - Kienle, Gunver S.; Mussler, Milena; Fuchs, Dieter; Kiene, Helmut
Background . Cancer patients widely seek integrative oncology which embraces a wide variety of treatments and system approaches. Objective . To investigate the concepts, therapeutic goals, procedures, and working conditions of integrative oncology doctors in the field of anthroposophic medicine. Methods . This qualitative study was based on in-depth interviews with 35 highly experienced doctors working in hospitals and office-based practices in Germany and other countries. Structured qualitative content analysis was applied to examine the data. Results . The doctors integrated conventional and holistic cancer concepts. Their treatments aimed at both tumor and symptom control and at strengthening the patient on different levels: living with the disease, overcoming the disease, enabling emotional and cognitive development, and addressing spiritual or transcendental issues according to the patient's wishes and initiatives. Therapeutic procedures were conventional anticancer and symptom-relieving treatments, herbal and mineral remedies, mistletoe therapy, art therapies, massages and other external applications, nutrition and lifestyle advice, psychological support, and multiple forms of empowerment. The approach emphasised good patient-doctor relationships and sufficient time for patient encounters and decision-making. Individualization appeared in several dimensions and was interwoven with standards and mindlines. The doctors often worked in teams and cooperated with other cancer care–related specialists. Conclusion . Integrative cancer care pursues an individualized and patient-centered approach, encompassing conventional and multimodal complementary interventions, and addressing, along with physical and functional needs, the emotional and spiritual needs of patients. This seems to be important for tumor and symptom control, and addresses major challenges and important goals of modern cancer care.